A Versatile Peroxidase from the Fungus Bjerkandera adusta Confers Abiotic Stress Tolerance in Transgenic Tobacco Plants - Hernández-Bueno, Nancy Sofia (Plants (Basel), 2021)
White-rot fungi are efficient lignin degraders due to the secretion of lignin peroxidase, manganese peroxidase, laccase, and versatile peroxidase (VP) on decayed wood. The VP is a high-redox-potential enzyme and could be used to detoxify reactive oxygen species (ROS), which accumulate in plants during biotic and abiotic stresses. We cloned the VP gene and expressed it via the Agrobacterium transformation procedure in transgenic tobacco plants to assay their tolerance to different abiotic stress conditions. Thirty independent T(2) transgenic VP lines overexpressing the fungal Bjerkandera adusta VP gene were selected on kanamycin. The VP22, VP24, and VP27 lines showed significant manganese peroxidase (MnP) activity. The highest was VP22, which showed 10.87-fold more manganese peroxidase activity than the wild-type plants and led to a 34% increase in plant height and 28% more biomass. The VP22, VP24, and VP27 lines showed enhanced tolerance to drought, 200 mM NaCl, and 400 mM sorbitol. Also, these transgenics displayed significant tolerance to methyl viologen, an active oxygen-generating compound. The present data indicate that overproducing the VP gene in plants increases significantly their biomass and the abiotic stress tolerance. The VP enzyme is an effective biotechnological tool to protect organisms against ROS. In transgenic tobacco plants, it improves drought, salt, and oxidative stress tolerance. Thus, the VP gene represents a great potential for obtaining stress-tolerant crops.